Creating a spatial knowledge database for protective functions in sustainable forest management: the case of Greece. (30th June 2021) - Raptis, Dimitrios; Kazana, Vassiliki; Stamatiou, Christos; Kazaklis, Angelos; Tsiaras, Stefanos
One of the basic indicators required to assess and monitor sustainable forest management at the national level within the mandatory for the EU countries FOREST EUROPE policy initiative concerns the area occupied by the protective forests. However, within this policy, no operational harmonised definition of the 'protective forest' term has been adopted to date, thus making it difficult to identify and map accurately the forest land area with protective functions. This paper presents a methodological approach for creating a spatial knowledge database for the protective functions related to soil, water, and infrastructure compatible with the FOREST EUROPE policy frame. The approach was implemented in Greece and it was found that about 40% of the country's productive forest land has an increased protection effect on soil and water, and about 15% of it on infrastructure.